Unearthing novel QTLs for enhancing rice straw quality through genome wide association mapping - Sah, R.P.; Subudhi, H.; Anilkumar, C.; Azharudeen, T.P.M.; Ravi, Devulapalli; Marndi, B.C.; Samantaray, S.; Behera, S.; Mohanty, S.P.; Varijakshapanicker, Padmakumar; Behera, L.; Anandan, A. (Range Management Society of India, 2025)
The potential of rice straw as an energy source for ruminants is substantial and depends on improving its cell wall composition through genetic enhancement. This study mapped quantitative trait loci (QTLs) for key straw quality traits, including dry matter, ash, nitrogen, lignin, silica, cellulose, hemicellulose, and digestibility using 133 rice lines genotyped with 133 SSR markers. A total of 37 significant marker-trait associations were detected, with eight markers influencing multiple traits and three linked to all traits except silica. Candidate genes included OsSND2, OsMYB55/OsPL and PGIP for cellulose content, OsNADH-GOGAT2 for nitrogen content and OsPG1 for hemicellulose content. These loci, genes and associated markers offer valuable tools for breeding dual-purpose rice varieties that combine high grain yield with superior, more digestible straw.